Kewenangan Penyidik Pegawai Negeri Sipil (PPNS) Keimigrasian dalam Penanganan Tindak Pidana Perdagangan Orang yang Berasal dari Tindak Pidana Penyelundupan Manusia - Lazuardi, Anggun; Ferdi, Ferdi; Elda, Edita (Universitas Ekasakti, 2023)
The practice of the crime of human smuggling (TPPM) is closely related to the practice of the crime of trafficking in persons (TPPO) which crosses national borders in jurisdiction. The practice of human smuggling allows for opportunities for the purpose of trafficking and exploitation of people who are smuggled across a country's borders. Handling is regulated in special criminal acts, namely the crime of human smuggling in Law Number 6 of 2011 with Immigration Civil Servant Investigators (PPNS) as law enforcement officers, while the crime of trafficking in persons is regulated in Law Number 21 of 2007 which only states said the investigator who could carry out the investigation. But the problem is, there is a practice of criminal acts of trafficking in persons originating from criminal acts of people smuggling, will Immigration Civil Servants have authority over this. However, Therefore, this research aims to analyze the authority of the Immigration Civil Servants in handling the criminal act of trafficking in persons originating from the criminal act of people smuggling. The results of the research show that the authority of the Immigration Civil Servants in handling the criminal act of trafficking in persons originating from the criminal act of people smuggling is to carry out joint investigations with Polri investigators. Based on the principle of lex specialis systematic, the crime of human smuggling is a more specific crime than the crime of trafficking in persons.